Measurement of optical properties and thermal diffusivity of vanadium dioxide nano-solution using thermal lens effect. (3rd January 2020) - Park, Hyun Woo; Jeong, Soo Yeol; Choi, Yeon Suk; Kim, Sok Won
The nonlinear optical coefficients (absorption and refractive index) and the thermal diffusivity of vanadium dioxide (VO2 ) solution were measured using the z-scan method and the thermal lens effect (TLE), respectively. A diode-pumped solid state (DPSS) laser with a wavelength of 532 nm and an intensity of 20 mW was used as light and heat source. The 50-nm-diameter spheres of VO2 were dispersed into ethylene glycol to make a 0.03% nano-solution. The obtained nonlinear absorption coefficient and the nonlinear refractive index at room temperature were 0.0068 m/W and 3.56 × 10 −12 m 2 /W, respectively. As the temperature was increased from room temperature to 65°C, the thermal diffusivity was decreased from 0.103 × 10 −6 to 0.044 × 10 −6 m 2 /s. Subsequently, the diffusivity began to increase up to 0.066 × 10 −6 m 2 /s at 75°C. Because of the low VO2 concentration, the obtained nonlinear coefficients were lower than those of other nano-solutions. The change in thermal diffusivity was caused by the phase transition at about 68°C, which is known as the metal-insulator transition (MIT) phenomenon of VO2 .